Final Cut Pro 6 : beyond the basics - Wohl, Michael (Apple Pro training series., 2008)
In this Apple-authorized training book, director and filmmaker Michael Wohl teaches advanced skills that editing professionals need to know most Each chapter presents a complete lesson in some aspect of video editing or finishing, with hands-on projects for readers to complete as they go. Michael Wohl shows how to master advanced trimming techniques, make polished transitions, work with nested sequences, edit multi-camera projects, create fantastic effects, color-correct your video, and composite like a pro. This text also covers Soundtrack Pro, shows you how to manage your clips and media, and throughout the book he offers dozens of helpful tips on improving your editing workflow The book's DVD offers plenty of professional footage and project files for you to use as you work your way through each book's lesson. Note: This book was written for Final Cut Pro 6, and is not intended to be used with Final Cut Pro 7. Certain lessons, including Lesson 3 Multicamera Editing and Lesson 10 Variable Speed, will result in sync errors and possible system crashes when used with Final Cut Pro 7.